Personality and sensation seeking in high-risk sports - Polona Klinar; Stojan Burnik; Tanja Kajtna (Palacký University Olomouc, 2017)
Background: Personality represents a relatively consistent and unique sum of psychological, cognitive and physical characteristics of an individual. Sensation seeking is defined as an action, characterized by the search for different, new, complex and intensive emotions and experiences and preparedness to take physical, social, legal and financial risks in order to achieve these experiences.Objective: We were looking for differences in personality and sensation seeking between high-risk sports athletes and recreational athletes and the correlation between one's purpose to participate in high-risk sports and actual participation.Method: The data was acquired using three different questionnaires: Sensation Seeking Scale (forms SSS - V and SSS - VI) and the Big Five Questionnaire. The sample consisted of 76 high-risk sports athletes and 51 recreational athletes. Data was analyzed using the SPSS statistical program.Results: The results were unexpected because we noticed differences between the two groups in which recreational athletes received higher results, especially in openness. Mostly results from such research show the converse - athletes of high-risk sports are more open. We did not find any difference between the two groups in sensation seeking. We found some correlations between personality traits and factors of Sensation Seeking Scale (SSS - V and SSS - VI). Openness and the Thrill and adventure seeking factor correlated in both versions of SSS.Conclusions: We conclude that high-risk sports athletes differ from recreational athletes, especially in openness. Also, we can confirm that both used versions of SSS are equally effective for analyzing sensation seeking.